Regeneração natural em floresta ribeirinha no norte do Pantanal - Nascimento, Felipe Silva Ovando do (2023)
The Pantanal is the largest intracontinental wetland in the world; its ecosystem contributions range from aquifer recharge, habitat for fauna and flora, retention of atmospheric carbon to nutrient cycling. The Pantanal had 8.5 million hectares affected by forest fires in 2020, significantly impacting local biodiversity and causing great national and international repercussion. Areas of different phytophysiognomies had their vegetation cover decimated by fire. In order to understand the response of natural regeneration in burned areas in periods of aquatic-terrestrial transitions, data collection was carried out respecting the two Pantanal hydrological periods, drought and flood. The study areas were two fragments of riparian forest, being: area 01 - area affected by forest fires with less intensity; area 02 - area affected by forest fires with greater intensity, characterized by the felling of the tree stratum. The NDVI index was evaluated for vegetation cover of the areas and the inventory of natural regeneration. The NDVI indexes show the passage of fire in the studied areas. The natural regeneration inventory showed an increase in the number of individuals after the flooding in area 01. The flood pulse acted directly on the contribution of regenerating individuals in area 01, besides the contribution of species dispersed by the local fauna. In area 02, natural regeneration showed an incipient quantity of species and individuals after the flooding, with no positive indicators that point to the reestablishment of the tree structure in the area in the short and medium term. However, in riparian areas where forest fires did not cause the elimination of the tree stratum and the ground cover was not dominated by opportunistic herbaceous species, natural regeneration showed better conditions for recovery of the area.